Preparation of biodiesel from waste cooking oil catalyzed by basicionic liquid - Ullah, Z. (Trans Tech Publications Ltd, 2014)
A basic ionic liquid tetra butyl phosphonium hydroxide was applied as a catalyst for biodiesel production from waste cooking oil by transesterification process and the yield 82 was achieved. The ionic liquid was used four times without any dramatic decrease in ester yield. And the methyl ester was checked by 1H NMR. Â© 2014 Trans Tech Publications, Switzerland.